CHANGES OF LIPID PEROXIDATION IN CONDITIONS OF CORRECTION OF HYPOTHYROSIS BY “IODIDE-100” DRUG AND α-TOKOPHEROL - Тучак, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In experiments on laboratory rats the influence of α-tokopherol on the state of organism’s free radical oxidation under conditions of complex correction of experimental hypothyrosis has been studied. As a result of investigation it has been determined that under the usage of “Iodide-100” drug the indexes of lipid peroxidation were inhibited insignificantly. In combined correction of hypothyrosis by iodide-100 and α-tokopherol a significant decrease of lipid peroxidation indexes has been determined and the abovementioned indexes not significantly differed from the analogous data in intact animals. Obtained data testify about the expediency of the usage of α-tokopherol for the complex correction of hypothyrosis.